2007
DOI: 10.1021/ac071402t
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Performance of an Ultrasonic Particle Focusing Flow Cytometer

Abstract: Creation of inexpensive small-flow cytometers is important for applications ranging from disease diagnosis in resource-poor areas to use in distributed sensor networks. In conventional-flow cytometers, hydrodynamics focus particles to the center of a flow stream for analysis, which requires sheath fluid that increases consumable use and waste while dramatically reducing instrument portability. Here we have evaluated, using quantitative measurements of fluorescent microspheres and cells, the performance of a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 32 publications
0
74
0
Order By: Relevance
“…Alternatively, acoustic focusing (15) can be used to analyze particles and cells (16). Dron et al demonstrated acoustic focusing of particles in a planar microchannel using a standing acoustic wave (41).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, acoustic focusing (15) can be used to analyze particles and cells (16). Dron et al demonstrated acoustic focusing of particles in a planar microchannel using a standing acoustic wave (41).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…When analyzing micro particles, focusing of the sample stream is usually applied to restrict their trajectories inside the flow channel (1,3,5,6,(8)(9)(10)(11)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). This positioning serves to increase signal stability when measuring particle properties and to avoid surface fouling in microfluidic channels.…”
mentioning
confidence: 99%
“…60 Combining these approaches enables development of a simpler device, with fewer options for the operator, and potentially more sustainable operation. A lost-cost, portable flow cytometer is being developed currently at Los Alamos National Laboratory using innovative approaches such as acoustic energy, rather than large volumes of sheath fluid, to focus particles to the center of a flow stream 21 ; low-cost light sources such as laser pointer modules 24 ; and open, reconfigurable digital data acquisition systems. 46 The availability of a ''minimalist'' flow cytometer 29 would immediately improve the quality of medical care that is available to diagnose and treat infectious diseases in poor regions of the world, which could in turn have a positive impact on international security.…”
Section: Monitoring Host Immune Response To Infectionmentioning
confidence: 99%
“…For instance, Shi et al 17,18 used a standing surface acoustic waves (SSAWs) method to realize on-chip micro-particle focusing. Goddard et al 19 evaluated the performance of a flow cytometer that used acoustic energy to focus particles/cells to the center of a flow stream. Suthanthiraraj et al 20 presented the one-dimensional acoustic standing waves for focusing of flowing cells and particles in a rectangular flow channel.…”
Section: Introductionmentioning
confidence: 99%